Makanan Ultra-Proses Berperan sebagai Mediator Hubungan Ketahanan Pangan dengan Status Kelebihan Gizi atau Obesitas pada Dewasa: Literature Review: Ultra-Processed Food can be a Mediator between Food Security Status and Overweight or Obesity among Adults: A Literature Review - Farah Faza; Unun Fitry Febria Bafani; Idri Iqra Fikha (Amerta Nutrition, 2023)
Background: The ultra-processed food (UPF) contributed 20-85% of total daily calories. The consumption of UPF can be triggered by food security status. Many studies revealed that UPF consumption has a direct negative impact on health, mainly in overweight and obesity.  Objectives: To review published studies assessing food security, UPF consumption, and overweight or obesity and find the possible links between those three factors. Methods: A literature review of scientific articles about food security, UPF consumption, and overweight or obesity, selected systematically according to the PRISMA Diagram. All articles were gathered through medical search engines, including PubMed, ScienceDirect, and Scopus, from December 2021 to February 2022. The bias risk of each selected paper was assessed using the checklist from The Joanna Briggs Institute (JBI) Critical Appraisal. Peer review and group discussions were performed to assess the quality of all articles gathered as objectively as possible using the STROBE Checklist. A narrative synthesis approach was opted to unify all findings across included studies systematically.  Results: Nineteen (19) scientific published papers were filtered. The association between food security status and UPF consumption showed inconsistent findings. However, UPF consumption revealed a consistent association with overweight/obesity, where the higher the UPF intake, the greater odds of being overweight/obese. The relationship between food security status and overweight or obesity tended to have a similar pattern. In high-income countries, the association was negative (the more food insecure, the higher overweight or obesity), while in low- and middle-income countries showed the opposite. The pathway could be: (1) food-insecure adults have higher UPF intake, hence gaining body weight, or (2) food-secure adults have higher UPF intake, hence gaining body weight.  Conclusions: UPF consumption is indicated as a potential mediator for food security status and nutritional status (overweight/obesity) through two pathways involving socio-demographic factors, psychological factors, social protections, and food choice motives.